Obvladovanje dejavnikov tveganja za nastanek srčno-žilnih bolezni v referenčni ambulanti družinske medicine - Terbovc, Alenka (Obzornik zdravstvene nege, 2017)
Introduction: The model of reference family medicine clinics is introducing changes to the treatment of patients at the primary health level. The purpose of the study was to explore the risk factors that contribute to reducing the occurrence of cardiovascular disease using non-pharmacological approaches in patients who are treated in a reference medicine family clinic. Methods: A retrograde survey was carried out on the data of the patients, who were treated in reference clinics for cardiovascular risk. The random study sample covered 128 patients, who passed the screening tests and control measurements in a reference medicine family clinic in the period from 1 May to 25 August 2014. Data were analysed using descriptive statistics and chi-square test. Results: Screening tests revealed a higher share of patients with acceptable measured parameters for blood pressure (41.6 %), cholesterol (45.5 %) and blood sugar (53.3 %) while the percentage of smokers decreased by 4 %. High cardiovascular risk (20-40 %) has reduced to 28.0 %, whereas extremely high cardiovascular risk decreased to 6.6 %. After the treatment in the clinic, the percentage of people performing physical activity 2-4 times per week increased to 54.3 % while 19.4 % of respondents reported physical activity 5 times per week. Statistically significant differences were demonstrated for blood pressure (x2 = 8.780, p = 0.003) and cholesterol (x2 =4.781, p = 0.029). Discussion and conclusions: Patients have significantly improved risk factors due to quality treatment that is enabled by the model of reference medicine clinics and the essential role of registered nurses in this model.
Keywords: diplomirane medicinske sestre; kakovost; kazalniki; quality; quality indicators; registered nurse